Side effects of Neemark (Azadirachta indica A. Juss) and two new vegetable oils formulations on Tetranychus urticae Koch and its predator Phytoseiulus persimilis Athias-Henriot (Bollettino di zoologia agraria e bachicoltura, 2024)
The effects of Neemark, commercial preparation obtained by neem(Azadirachta indica) seed kernels extract, on Tetranychus urticae Koch and Phytoseiuluspersimilis Athias-Henriot were tested on bean leaf discs treated with differentconcentrations in laboratory experiments. Neemark can be considered moderatelytoxic for T. urticae but highly toxic for young stages and adults of Ph.persimilis at 3% and 5% concentrations. Also were investigated two new vegetableoils formulations 7094 and 1294 D/S on T. urticae in concentrations 0.5%,1 % and 2% caused high toxicity and promise for the near future an alternativesolution in the control of tetranychids in greenhouse culture and field crops.
Keywords: Neemark; vegetable oils formulations; Tetranychus urticae; Phytoseiulus persimilis